Direct analysis of fulvic acids adsorbed onto capped gold nanoparticles by laser desorption ionization Fourier-transform ion cyclotron resonance mass spectrometry. Issue 8 (9th July 2021) - Giannopoulos, Konstantinos; Benettoni, Pietro; Holbrook, Timothy R.; Reemtsma, Thorsten; Wagner, Stephan; Lechtenfeld, Oliver J.
Abstract : Laser desorption ionization Fourier-transform ion cyclotron resonance mass spectrometry for direct molecular characterization of nanoparticle coronas. Abstract : Natural organic matter (NOM) adsorption on nanoparticle (NP) surfaces in natural waters forms a corona that can alter NP properties and its environmental fate. Anthropogenic NPs are usually coated with an organic capping agent that may, in turn, influence the extent and molecular composition of the corona. Up-to-now, the molecular composition of the NOM corona can only be analyzed in controlled experiments due to a lack of appropriate direct surface analysis methods. Here, we introduce laser desorption ionization Fourier-transform ion cyclotron resonance mass spectrometry (LDI-FT-ICR-MS) to directly analyze Suwannee River Fulvic Acid (SRFA) after adsorption and sequential desorption on gold (Au) NPs capped with small molecules (citric acid (CA), tannic acid (TA), lipoic acid (LA)) and large polymers (polyvinylpyrrolidone (PVP), branched polyethylenimine (BPEI), methoxy polyethylene glycol sulfhydryl (m-PEG-SH)). LDI-FT-ICR-MS revealed differences in the molecular composition of the NP corona depending on the capping agents' chemistry. Positively charged BPEI efficiently adsorbed larger oxygen-rich aromatics whereas negatively charged CA and LA adsorbed oxygen-containing aromatics. The weak negative PVP adsorbed oxygen-containing aliphatics and non-charged m-PEG-SH small oxygen-depleted aliphatics, both with lower efficiency. However, TA preferentially adsorbed polyphenolic compounds from SRFA due to its similar chemistry. Further comparison of the Au-CA corona with the conventional indirect electrospray ionization (ESI)-FT-ICR-MS analysis largely confirmed the results of the new direct LDI analysis. Due to the higher sensitivity of the direct method, LDI-FT-ICR-MS can be applied to environmentally relevant NOM : NP ratios which was not possible before. LDI-FT-ICR-MS is a promising method to study the extent and molecular composition of NP coronas and suitable to better elucidate NP fate in the environment.